Study of structure and μstructure evolution of i-Al64Cu23Fe13 quasicrystal subjected to ball milling processes - Pillaca, M. (2012)
In the present work we perform the systematic study, employing X-ray diffraction and Mössbauer spectrometry, of the variation of the structural and hyperfine parameters during the milling process of the icosahedral Al64Cu23Fe13 quasicrystal. For this purpose, the samples were prepared by arc-furnace technique followed by heat treatment. Then, the samples were nanoestructured in a high energy ball milling equipment during 5, 10, 15, 20, 45, 50 and 60 hours. The X-ray diffraction patterns show the stability of the nanoestructured samples. Furthermore, the Mössbauer spectra indicate the increase of the Fe-sites in the grain boundary during the milling process.